PERENCANAAN PAJAK UNTUK EFISIENSI PEMBAYARAN PAJAK - Imam Nazarudin Latif Andi Kantono (Prodi Ilmu Administrasi Negara, 2015)
The purpose of this study was to determine the calculation ofincome tax PT. Kaltim Lestari Unggul before and after applicable tax planning to improve the efficiency of the paymentof tax burden. The analysis tools being used was Number of tax laws. 36 of 2008, Fiscal correction of the costs included in Law No. taxation. 36 of 2008, Calculating and tax planning on tax payer income tax in 2012, comparing taxable income before and after tax planning. Based on the results of a study of the income statement of PT. Kaltim Lestari Unggul, it had been found that payment ofincome tax expense using the right tax planning in accordance with the provisions of the tax laws No.36 of 2008 in PT. Kaltim Lestari Unggul in 2012 to minimize the burden of the tax to be paid.